Islamic economics principles & analysis - Adam Abdullah (International Shari'ah Research Academy for Islam Finance (ISRA), 2018)
With the impressive emergence of Islamic finance as a branch of Islamic economics, the need for a solid knowledge base that encompasses theories, thoughts and applications related to the subject increased in importance. However, writing about Islamic economics is a great challenge due to the differences in opinion on many of its issues. This includes methodologies for determining the Islamic perspective on economic concepts and issues as well as applicable solutions for today's economic and social problems. It is further argued that Islamic economics topics are not as clear as those in conventional economics as they have their own religious, spiritual and social dimensions. The points of controversy have generated lengthy discussions. Moreover, Islamic economics encompasses a vast array of topics and approaches, from the purely theoretical, which may include philosophy or religious ideas, to mathematical and quantitative analyses. We tried our best throughout this textbook to simplify, clarify and summarise these concepts to make them accessible to all readers including students, practitioners, academics and even interested non-specialists.